A Front Surface Optimization Study for Photovoltaic Application - A. Nawabjan; F. Iqbal; A. S. Abdullah (Universitas Ahmad Dahlan, 2018)
In this paper, we presented a possible front surface optical enhancement of Si solar cell by optimizing the Antireflection (AR) and light trapping (LT) schemes. Conventional plasma enhanced chemical vapor deposition (PECVD) and in house hot wire chemical vapor deposition (HWCVD) tool was used to deposit Silicon Nitride (SiNX) layer and optimized at 668nm wavelength. This was followed by surface texturing of random pyramids to further enhance the broadband reflectance of the front surface. Broadband reflectance measurement using integrating sphere method showed achieved weighted average reflectance (WAR) value of as low as 1.8% and 1.5%, when 85nm SiNX was deposited on top of random pyramids structure using HWCVD and PECVD methods, respectively.